The Impact of Quality Assurance Policies on Curriculum Development in Ontario Postsecondary Education - Liu, Qin (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
Two trends in the evolution of quality assurance in Canadian postsecondary education have been the emergence of outcomes-based quality standards and the demand for balancing accountability and improvement. Using a realist, process-based approach to impact analysis, this study examined four quality assurance events at two universities and two colleges in Ontario to identify how system-wide quality assurance policies have impacted the curriculum development process of academic programs within postsecondary institutions. The study revealed different approaches that postsecondary institutions chose to use in response to quality assurance policies and the mechanisms that may account for different experiences. These mechanisms include endeavours to balance accountability and continuous improvement, leadership support, and the emerging quality assurance function of teaching and learning centres. These findings will help address the challenges in quality assurance policy implementation within Canadian postsecondary education and enrich international discussions on the accountability-improvement dichotomy in the context of quality assurance.